Sistem Penentuan Pemberian Surat Izin Gangguan pada Industri menggunakan Multi Factor Evaluation Process - Bella Nadila; Ruri Ashari Dalimuthe; Adi Mas Afandi (Universitas Hamzanwadi, 2022)
Establishing a business or industrial place must obtain a permit from the government which aims to protect the surrounding community to be protected from the possibility of disturbance or pollution caused by the industry. Therefore, in order to achieve this, it is necessary to have a system that automatically provides accurate and quick decisions in determining which company or industry is worthy of being granted a business license. The purpose of this study is to build a decision support system in determining business premises or industry hinder ordonantie permits using the Multi-Factor Evaluation Process (MFEP) method. This research stage consists of analysis, design, testing, and implementation adopted from the waterfall model. Data collection was carried out by interviews and observations. The data analysis technique used is the MFEP method to determine the final decision in granting nuisance permits to companies or industries. Samples or training data totaling 30 industry names in the Asahan Regency area. This system is tested with a black box which aims to find out if all components in the system are running well. Our findings show that the system we have created is appropriate based on the results of the analysis using the MFEP method. In addition, the results of black box testing show that all components in this system are valid and functioning properly.